A high-stability boron-containing polymer catalyst and preparation method thereof
By ultrasonic treatment of BOPs in ethanol aqueous solution and reaction with Na2PdCl4 under ultrasonic synergistic microwave process, a highly stable BOPs@Pd catalyst was prepared, which solved the problem of insufficient stability and catalytic activity of existing boron polymer catalysts and achieved Good ammonia borane hydrolysis and photocatalytic properties.
Patent Information
- Application Number
- CN202410764807.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The stability and catalytic activity of existing boron polymer catalysts are insufficient, and the catalytic performance is single, making it difficult to meet the needs of complex chemical reactions.
BOPs were ultrasonically treated in an ethanol aqueous solution and reacted with Na2PdCl4 under ultrasonic synergy with microwave technology to prepare a highly stable BOPs@Pd catalyst. This method uses the synergistic effect of ultrasound and microwave to shorten the reaction time, improve the preparation efficiency, and improve the reaction conditions through ethanol solution.
The prepared BOPs@Pd catalyst shows good ammonia borane hydrolysis catalytic activity and photocatalytic activity, and has high stability. It can maintain excellent catalytic performance after repeated use, reduce the dosage of the catalyst and extend its service life. .
Smart Images

Figure BDA0004892109300000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a high-stability boron-containing polymer catalyst and a preparation method thereof. Background Art
[0002] Boron polymer catalysts are a class of compounds containing boron elements that play a catalytic role in catalytic reactions. These catalysts have important application value in organic synthesis and chemical reactions, and can promote the reaction, increase the reaction rate, and reduce the activation energy of the reaction. There are various types of boron polymer catalysts, including boric acid, borate salts, boric esters, etc. They are often used in organic synthesis reactions to catalyze important reactions such as boron reduction, boron alcohol condensation, and boric ester asymmetric catalysis. Boron polymer catalysts have many advantages, such as good catalytic effect, mild reaction conditions, and easy separation and recovery of catalysts. Therefore, boron polymer catalysts are widely used in the field of organic synthesis and have been widely recognized in laboratories and industrial production.
[0003] Researching and developing highly stable boron-containing polymer catalysts can not only promote the reaction and improve the reaction yield, but also reduce the amount of catalyst used and extend the service life of the catalyst, which is of great significance in the field of catalysis.
[0004] Secondly, the catalytic performance of the boron polymer catalyst prepared by the current method is single, and the process needs to be further optimized while improving the catalytic activity. Summary of the invention
[0005] In view of this, the present invention proposes a highly stable boron-containing polymer catalyst and a preparation method thereof, which has good ammonia borane hydrolysis catalytic activity and photocatalytic activity and has high stability.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0008] (1) adding BOPs to a 1-3 wt % ethanol aqueous solution and ultrasonically treating the solution to obtain a BOPs solution;
[0009] (2) then adding a Na2PdCl4 aqueous solution to the BOPs solution, and treating the solution with an ultrasonic-assisted microwave process for 8 to 12 minutes, wherein the ultrasonic frequency is 25 to 35 kHz, the microwave frequency is 2600 to 2800 MHz, and the temperature is 20 to 30°C;
[0010] (3) The filter cake was collected by filtration and washed with deionized water, and then dried under vacuum conditions to obtain solid BOPs@Pd.
[0011] Furthermore, in step (1), the solid-liquid ratio of BOPs to ethanol aqueous solution is 1 g:100-120 mL, and the ultrasonic treatment time is 2-3 min.
[0012] Furthermore, in step (2), the rate of adding the Na2PdCl4 aqueous solution is 8 to 12 ml / min.
[0013] Furthermore, in step (2), the concentration of the Na2PdCl4 aqueous solution is 0.03-0.04 mol / L; and the molar mass ratio of Na2PdCl4 to BOPs is 24-25 mM:1 g.
[0014] Furthermore, in step (3), the drying temperature is 55 to 65° C. and the drying time is 2 to 4 hours.
[0015] Furthermore, the preparation method of BOPs comprises the following steps: S1, adding 4,4'-bipyridine to an aqueous acetic acid solution to obtain a 4,4'-bipyridine solution; S2, taking Cs2B 12 H 12 Add to acetic acid aqueous solution to obtain Cs2B 12 H 12 Solution; Cs2B 12 H 12 The solution is added to the 4,4'-bipyridine solution, stirring is stopped after a precipitate is formed, the mixture is allowed to stand for 6 to 8 hours, and filtered to obtain a solid, namely BOPs.
[0016] Furthermore, Cs2B 12 H 12 The molar ratio of acetic acid to 4,4'-bipyridine is 1:5 to 5.1; the pH value of the acetic acid aqueous solution is 2.8 to 3.2;
[0017] In step S1, the material-liquid ratio of 4,4'-bipyridine to acetic acid aqueous solution is 1 mol:35-38 L;
[0018] In step S2, Cs2B 12 H 12 The material-liquid ratio to the acetic acid aqueous solution is 1 mol:9~11L.
[0019] Furthermore, the Cs2B 12 H 12 The preparation method comprises the following steps: taking [Et3NH]2[B 12 H 12 ] is added to ultrapure water, and then CsOH is added. The solvent is slowly evaporated in an electric heating mantle at 250°C until no ammonia smell is emitted. Then it is naturally cooled to room temperature and ethanol is added. Then the generated ethanol-containing crystals are filtered. Then the crystals are added to pure water and evaporated to dryness to obtain pure Cs2B 12 H12 .
[0020] Furthermore, [Et3NH]2[B 12 H 12 ] and CsOH mass ratio is 1:0.8~0.9; [Et3NH]2[B 12 H 12 ]The material-liquid ratio of ultrapure water, ethanol and pure water is 1g:55~60mL:55~60mL:25~30ml.
[0021] A method for preparing a high-stability boron-containing polymer catalyst is prepared by any method described in the present invention.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The solid BOPs@Pd catalyst prepared by the method of the present invention exhibits good ammonia borane hydrolysis catalytic activity and photocatalytic activity, and has high stability. It can still maintain its excellent catalytic performance after multiple uses. It has reliability and durability in practical applications, can reduce the amount of catalyst used, and extend the service life of the catalyst.
[0024] Among them, the present invention uses ethanol aqueous solution to prepare BOPs solution, which can better react with Na2PdCl4; the reaction process of BOPs and Na2PdCl4 in the present invention adopts ultrasonic synergistic microwave process to greatly shorten the reaction time and improve the preparation efficiency. The preparation process of BOPs in the present invention uses acetic acid solution to accelerate the formation of product precipitation and effectively shorten the standing time. DETAILED DESCRIPTION
[0025] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0026] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0027] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0028] CsOH: cesium hydroxide;
[0029] Na2PdCl4: sodium tetrachloropalladate hydrate;
[0030] [Et3NH]2[B 12 H 12]: According to the method in the literature, 400 mL of diethylene glycol dimethyl ether and 100.0 g of sodium borohydride were added to a round-bottom flask (2 L) protected by a nitrogen flow, and heated in a constant temperature (100°C) oil bath for 1 h to obtain a suspension A; 205.0 g of elemental iodine was dissolved in diethylene glycol dimethyl ether (350 mL) to obtain a diethylene glycol dimethyl ether iodine solution; the above diethylene glycol dimethyl ether iodine solution was slowly added to the suspension A using a constant pressure dropping funnel, and the flow rate was controlled to ensure that the entire iodine solution was added within 6 h; when the iodine was added, the reaction was continued at 100°C overnight to obtain a light yellow transparent solution; the oil bath temperature was then slowly raised to 190°C±5°C and kept warm for pyrolysis for 16 h; after the pyrolysis was completed, it was naturally cooled to 25°C and a white solid was waited to condense on the round bottom flask, pour out the supernatant; then remove diethylene glycol dimethyl ether by reduced pressure distillation at 130°C to recover a small amount of white solid product in the solvent; pour the remaining white solid into a 2L flask containing a large amount of product, and then slowly add 600mL of cold water; then transfer the solution to a beaker, slowly drop 280mL of concentrated hydrochloric acid, after the dropwise addition is complete, put the beaker into a low temperature (<5°C) water bath and let it stand for 12h to allow the generated boric acid to crystallize out; filter to remove the precipitated boric acid, and then add 400mL of triethylamine to the filtrate to generate a large amount of white solid; after standing for 12h, filter and collect the white solid, and put it into hot water (50°C), collect the solid while hot to remove the residual boric acid, and obtain the target [Et3NH]2[B 12 H 12 ].
[0031] Preparation Example 1
[0032] CxB 12 H 12 Preparation: Take [Et3NH]2[B 12 H 12 ] was added to ultrapure water, followed by CsOH, [Et3NH]2[B 12 H 12 The mass ratio of ] to CsOH is 1:0.85; the solvent is slowly evaporated in an electric heating mantle at 250°C until no ammonia smell is emitted, then naturally cooled to room temperature, and ethanol is added; then the generated ethanol-containing crystals are filtered; then the crystals are added to pure water and evaporated to dryness to obtain pure Cs2B 12 H 12 .
[0033] The above [Et3NH]2[B 12 H 12 ]The material-liquid ratio of ultrapure water, ethanol and pure water is 1g:58mL:58mL:28ml.
[0034] Preparation Example 2
[0035] Preparation of BOPs:
[0036] S1, adding 4,4'-bipyridine to an acetic acid aqueous solution with a pH value of 3.0, the solid-liquid ratio of 4,4'-bipyridine to the acetic acid aqueous solution is 1 mol:37L, to obtain a 4,4'-bipyridine solution;
[0037] S2, take Cs2B from Preparation Example 1 12 H 12 Added to the acetic acid aqueous solution with pH value of 3.0, Cs2B 12 H 12 The molar ratio of Cs2B to 4,4'-bipyridine is 1:5.0. 12 H 12 The material-liquid ratio with acetic acid aqueous solution is 1 mol:10 L to obtain Cs2B 12 H 12 Solution; Cs2B 12 H 12 The solution was added to the 4,4'-bipyridine solution, stirring was stopped after a precipitate was formed, the mixture was allowed to stand for 7 hours, and filtered to obtain a solid, namely BOPs.
[0038] Example 1
[0039] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0040] (1) adding the BOPs solid prepared in Preparation Example 2 into a 2 wt % ethanol aqueous solution and subjecting the mixture to ultrasonic treatment to obtain a BOPs solution;
[0041] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:110 mL, and the ultrasonic treatment time was 2.5 min.
[0042] (2) Then, 0.035 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution, the addition rate of the Na2PdCl4 aqueous solution was 10 ml / min, the molar mass ratio of Na2PdCl4 to BOPs was 24.5 mM:1 g, and the solution was treated by ultrasonic-assisted microwave process for 10 min, the ultrasonic frequency was 30 KHz, the microwave frequency was 2700 MHz, and the temperature was 25±2°C;
[0043] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0044] Example 2
[0045] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0046] (1) adding the BOPs solid prepared in Preparation Example 2 into a 1 wt % ethanol aqueous solution and subjecting the mixture to ultrasonic treatment to obtain a BOPs solution;
[0047] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:100 mL, and the ultrasonic treatment time was 3 min.
[0048] (2) Then, a 0.03 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution, the addition rate of the Na2PdCl4 aqueous solution was 8 ml / min, the molar mass ratio of Na2PdCl4 to BOPs was 24 mM:1 g, and the solution was treated by ultrasonic-assisted microwave process for 12 min, the ultrasonic frequency was 25 KHz, the microwave frequency was 2600 MHz, and the temperature was 25±2°C;
[0049] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0050] Example 3
[0051] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0052] (1) adding the BOPs solid prepared in Preparation Example 2 into a 3 wt % ethanol aqueous solution and subjecting the mixture to ultrasonic treatment to obtain a BOPs solution;
[0053] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:120 mL, and the ultrasonic treatment time was 2 min.
[0054] (2) Then, a 0.04 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution, the addition rate of the Na2PdCl4 aqueous solution was 12 ml / min, the molar mass ratio of Na2PdCl4 to BOPs was 25 mM:1 g, and the solution was treated by ultrasonic-assisted microwave process for 8 min, the ultrasonic frequency was 35 KHz, the microwave frequency was 2800 MHz, and the temperature was 25±2°C;
[0055] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0056] Comparative Example 1
[0057] The main difference from Example 1 is that the treatment process of step (1) is different, and the BOPs solid is added to deionized water:
[0058] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0059] (1) adding the BOPs solid prepared in Preparation Example 2 into deionized water and performing ultrasonic treatment to obtain a BOPs solution;
[0060] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:110 mL, and the ultrasonic treatment time was 2.5 min.
[0061] (2) Then, 0.035 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution, the addition rate of the Na2PdCl4 aqueous solution was 10 ml / min, the molar mass ratio of Na2PdCl4 to BOPs was 24.5 mM:1 g, and the solution was treated by ultrasonic-assisted microwave process for 10 min, the ultrasonic frequency was 30 KHz, the microwave frequency was 2700 MHz, and the temperature was 25±2°C;
[0062] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0063] Comparative Example 2
[0064] The main difference from Example 1 is that the treatment process of step (1) is different, and the BOPs solid is added to the methanol aqueous solution:
[0065] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0066] (1) adding the BOPs solid prepared in Preparation Example 2 into a 3 wt % methanol aqueous solution and subjecting the mixture to ultrasonic treatment to obtain a BOPs solution;
[0067] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:110 mL, and the ultrasonic treatment time was 2.5 min.
[0068] (2) Then, 0.035 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution, the addition rate of the Na2PdCl4 aqueous solution was 10 ml / min, the molar mass ratio of Na2PdCl4 to BOPs was 24.5 mM:1 g, and the solution was treated by ultrasonic-assisted microwave process for 10 min, the ultrasonic frequency was 30 KHz, the microwave frequency was 2700 MHz, and the temperature was 25±2°C;
[0069] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0070] Comparative Example 3
[0071] The main difference from Example 1 is that the treatment process in step (2) is different. Instead of using ultrasonic and microwave technology, a longer stirring time is used:
[0072] A method for preparing a highly stable boron-containing polymer catalyst comprises the following steps:
[0073] (1) adding the BOPs solid prepared in Preparation Example 2 into a 2 wt % ethanol aqueous solution and subjecting the mixture to ultrasonic treatment to obtain a BOPs solution;
[0074] The solid-liquid ratio of BOPs to ethanol aqueous solution was 1 g:110 mL, and the ultrasonic treatment time was 2.5 min.
[0075] (2) Then, 0.035 mol / L Na2PdCl4 aqueous solution was added to the BOPs solution at a rate of 10 ml / min, with a molar mass ratio of Na2PdCl4 to BOPs of 24.5 mM:1 g, and the mixture was stirred at 25±2°C for 2 h;
[0076] (3) The filter cake was collected by filtration and washed with deionized water, and then dried at 60 °C under vacuum conditions for 3 h to obtain solid BOPs@Pd.
[0077] Test Example 1 - Catalytic Hydrogen Decomposition Test of Ammonia Borane Water
[0078] Ammonia borane (NH3BH3, AB) is one of the important materials for chemical hydrogen storage, with a high hydrogen capacity of 19.6wt%, high solubility and long-term stability in solution at room temperature.
[0079] The solid BOPs@Pd catalysts prepared in Examples 1-3 and Comparative Examples 1-3 were used to test the ability of ammonia borane (NH3BH3, AB) to decompose hydrogen from water. In the test of catalyzing the hydrolysis of AB at 25°C, the input amount of the solid BOPs@Pd catalyst was 2.0 mg, and the test results are shown in Table 1.
[0080] Table 1 Catalytic activity for hydrolysis of ammonia borane
[0081]
[0082] As can be seen from Table 1, the solid BOPs@Pd catalysts prepared in Examples 1-3 have good catalytic activity for the hydrolysis of ammonia borane. Compared with Comparative Examples 1-3, the TOF value of the solid BOPs@Pd catalysts prepared in Examples 1-3 is significantly improved, and the solid BOPs@Pd catalysts prepared in Examples 1-3 have a stronger advantage in the catalytic performance of the hydrolysis of ammonia borane.
[0083] Test Example 2-Photocatalytic Activity Test
[0084] 200mL of methyl orange dye solution (6mg / L) was placed in a conical flask, and 0.1mg of solid BOPs@Pd catalyst was added to the conical flask, and stirred evenly to fully mix with the methyl orange dye solution. After mixing, the mixed solution was placed under a 30W, 253.7nm ultraviolet lamp for illumination reaction, and samples were taken at 0min, 30min, 60min, and 90min of reaction, respectively. The absorbance of the methyl orange dye solution was measured using a spectrophotometer, and the reaction rate constant was calculated based on the curve of absorbance change over time.
[0085] Table 2 Photocatalytic decolorization efficiency of methyl orange
[0086] <![CDATA[Reaction rate constant (h -1 )]]> Example 1 2.98 Example 2 2.61 Example 3 2.52 Comparative Example 1 1.51 Comparative Example 2 1.82 Comparative Example 3 1.43
[0087] As can be seen from Table 2, the solid BOPs@Pd catalysts prepared in Examples 1-3 exhibit good performance in terms of photocatalytic activity. Compared with Comparative Examples 1-3, the photocatalytic rate of the solid BOPs@Pd catalysts prepared in Examples 1-3 is significantly improved, showing a stronger advantage in photocatalytic performance.
[0088] Test Example 3-Stability Study
[0089] The stability of the solid BOPs@Pd catalyst prepared in Examples 1-3 was investigated. Ten repeated experiments were conducted for the catalytic hydrogen decomposition test of ammonia borane water and the photocatalytic decolorization test of methyl orange dye solution, and the results were compared.
[0090] The results show that after ten repeated experiments, the solid BOPs@Pd catalysts prepared in Examples 1-3 still exhibit good ammonia borane hydrolysis catalytic activity and photocatalytic activity, indicating that the solid BOPs@Pd catalysts prepared in Examples 1-3 have high stability.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly stable boron-containing polymer catalyst for use in photocatalytic decolorization of methyl orange, characterized in that: The preparation method of the catalyst comprises the following steps: (1) Add BOPs to 1-3 wt% ethanol aqueous solution and perform ultrasonic treatment to obtain a BOPs solution; The preparation method of BOPs comprises the following steps: S1, adding 4,4'-bipyridine into an acetic acid aqueous solution to obtain a 4,4'-bipyridine solution; S2, taking Cs2B 12 H 12 Add to acetic acid aqueous solution to obtain Cs2B 12 H 12 Solution; Cs2B 12 H 12 The solution was added to the 4,4'-bipyridine solution, and stirring was stopped after precipitation was formed. The mixture was allowed to stand for 6-8 hours and filtered to obtain a solid, namely BOPs. (2) Then, a Na2PdCl4 aqueous solution was added to the BOPs solution, and the solution was treated by ultrasonic-assisted microwave process for 8-12 min, with an ultrasonic frequency of 25-35 KHz, a microwave frequency of 2600-2800 MHz, and a temperature of 20-30 °C; (3) Collect the filter cake by filtration and wash it with deionized water, and then dry it under vacuum conditions to obtain solid BOPs@Pd.
2. The use according to claim 1, characterized in that: In step (1), the solid-liquid ratio of BOPs to ethanol aqueous solution is 1 g: 100-120 mL, and the ultrasonic treatment time is 2-3 min.
3. The use according to claim 1, characterized in that In step (2), the rate of adding the Na2PdCl4 aqueous solution is 8-12 ml / min.
4. The use according to claim 1, characterized in that: In step (2), the concentration of the Na2PdCl4 aqueous solution is 0.03-0.04 mol / L; the molar mass ratio of Na2PdCl4 to BOPs is 24-25 mM: 1 g.
5. The use according to claim 1, characterized in that: Step (3), the drying temperature is 55-65°C and the drying time is 2-4 hours.
6. The use according to claim 1, characterized in that: CxB 12 H 12 The molar ratio of acetic acid to 4,4'-bipyridine is 1:5-5.1; the pH value of the acetic acid aqueous solution is 2.8-3.2; In step S1, the material-liquid ratio of 4,4'-bipyridine to acetic acid aqueous solution is 1 mol: 35-38 L; In step S2, Cs2B 12 H 12 The solid-liquid ratio to the acetic acid aqueous solution is 1 mol: 9~11 L.
7. The use according to claim 1, characterized in that: The Cs2B 12 H 12 The preparation method comprises the following steps: taking [Et3NH]2[B 12 H 12 ] Add ultrapure water, then add CsOH, slowly evaporate the solvent in a 250 ℃ electric heating mantle until no ammonia smell is emitted, cool naturally to room temperature, add ethanol, then filter the generated ethanol-containing crystals, then add pure water to evaporate to dryness, and obtain pure Cs2B 12 H 12 .
8. The use according to claim 7, characterized in that: [Et3NH]2[B 12 H 12 ] and CsOH mass ratio is 1:0.8~0.9; [Et3NH]2[B 12 H 12 ]The material-liquid ratio with ultrapure water, ethanol and pure water is 1g: 55~60mL: 55~60mL: 25~30ml.
Citation Information
Patent Citations
Hydrogen production method by using proton-responsive iridium complex for catalysis of ammonia borane hydrolysis
CN104891435A
Carbon-supported palladium-gold nano heterogeneous catalyst as well as preparation method and application thereof
CN117282425A